The Functional Specialization of the Planum Temporale - Zheng, Zane Z. (American Physiological Society, 2009)
The planum temporale (PT) is an anatomically heterogeneous area with several architectonic subdivisions and extensive connections with other parts of the brain. Here I review a functional MRI study investigating the role of a functionally defined area (Spt) within the left PT in speech motor processing and discuss the functional properties of PT regions in the context of findings from recent neurophysiological and neuroimaging studies.